Comparison of the effects of barbiturate, benzodiazepine and ketamine on visual evoked potentials in rabbits - Castro, J. [UNESP]; Resende, Luan A.L. [UNESP]; Bertotti, M. F Z [UNESP]; Fonseca, Ronaldo Guimarães [UNESP]; Zanchetta, S. [UNESP]; Schelp, Arthur Oscar [UNESP] (My University, 2005)
The aim of this study was to compare the effects of barbiturate, benzodiazepine and ketamine on flash-evoked potentials (F-VEP) in adult rabbits. A total of 36 animals were studied, 16 after pentobarbital endovenous (EV) inffusion, 10 after midazolam EV administration, and 10 after ketamine EV inffusion. Pentobarbital induced triphasic F-VEP, first negative (N1), secondpositive (P1), third negative (N2) waves, all with large amplitudes and P1 with well-defined morphology. Mean P1 latency was 33ms. Midazolam induced similar but less defind triphasic waves, with mean latency of 27ms. Ketamine induced poliphasic and poorly defined F-VEP, with mean first positive (P1) latency of 27ms. Statistical analysis showed more elongated latency for the pentobarbital group than the midazolam and ketamine groups. The results of this study suggest that the pharmacological effects of pentobarbital and midazolam on GABA neurotransmission in rabbit visual cortex may be different; another neurotransmission system, possibly cholinergic, may be involved. The ketamine effect seen in rabbit visual cortex seems to be different from pentobarbital and midazolam.
Keywords: Ketamine; Midazolam; Pentobarbital; Visual evoked potentials; 4 aminobutyric acid; ketamine; midazolam; pentobarbital; amplitude modulation; animal experiment; cholinergic transmission; controlled study; drug effect; evoked visual response; female; GABAergic transmission; latent period; nonhuman; visual cortex; waveform; white light; Anesthetics, Dissociative; Animals; Body Temperature; Evoked Potentials, Visual; Female; Hypnotics and Sedatives; Phenobarbital; Rabbits; Visual Cortex